Analysis of Factors Influencing Mortality in Patients with Intracerebral Hemorrhagic Stroke - Nurlisa Naila Aulia; Shobihatus Syifak; Dyah Yuniati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
Stroke is a cerebrovascular disease that causes sudden neurological deficits due to the interruption of blood supply to the brain, resulting in the disruption of brain function. It is ranked as the second most common cause of death worldwide and leads to the highest number of disabilities globally. The incidence of this disease is 10-20 cases per 100,000 population, reaching 15% of all strokes worldwide yearly. The highest mortality rate was 20.3% after 48 hours and 18.3% less than 48 hours. This number is greater than the death rate in stroke infarction. This study aims to analyze the factors influencing mortality in patients with intracerebral hemorrhage (ICH). This type of research is observational analytic research. The design used is cross-sectional. This study was approved by the Health Ethics Committee of the Jemursari Islamic Hospital in Surabaya. The sampling technique uses total sampling. The total sample of this study was 65 patients. The sample in this study were all ICH stroke patients who were treated at RSI JS Surabaya from January 2019 to December 2021. Statistical analysis in this study used the chi-square correlation test. The results showed that the duration of hospitalization and bleeding volume had a significant correlation with the mortality in stroke patients (p-value<0.05) with OR (95% CI) are 0.243 (0.082-0.723) and 0.154 (0.048-0.500) respectively. Bleeding volume has a correlation with mortality in this study. However, this study has only fewer samples and it can’t be generalized.